2002
DOI: 10.1116/1.1463726
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced protective carbon coating for extreme ultraviolet optics

Abstract: A technique is described that uses radiation and a gas-phase species to produce a protective carbon coating on extreme ultraviolet (EUV) optics. A specific example is given in which a ∼5 Å carbon coating is deposited on EUV Mo/Si optics via coexposure to radiation (EUV photons, electrons) and ethanol vapor. Auger electron spectroscopy, sputter Auger depth profiling, and EUV reflectivity measurements are presented that suggest a carbon coating that is substantially void free and protects the optic from water-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…[3][4][5] It has been demonstrated that a carbonaceous film can be cleaned by using ozone 6 or atomic hydrogen. 12 Similar results have also been reported by Klebanoff et al 13 for a Si-capped multilayer sample that was irradiated mainly by a high-energy electron beam. The technology for a capping layer with which an oxidation-resistant Ru thin film was coated onto the surface of the mirror has been proposed and demonstrated.…”
Section: Introductionsupporting
confidence: 69%
“…[3][4][5] It has been demonstrated that a carbonaceous film can be cleaned by using ozone 6 or atomic hydrogen. 12 Similar results have also been reported by Klebanoff et al 13 for a Si-capped multilayer sample that was irradiated mainly by a high-energy electron beam. The technology for a capping layer with which an oxidation-resistant Ru thin film was coated onto the surface of the mirror has been proposed and demonstrated.…”
Section: Introductionsupporting
confidence: 69%
“…86,87 To understand this mitigation effect, one has to bear in mind that the addition of alcohols switches the originally oxidizing EUVL environment into a net reducing environment. 86,87 To understand this mitigation effect, one has to bear in mind that the addition of alcohols switches the originally oxidizing EUVL environment into a net reducing environment.…”
Section: Interaction Of Hydrocarbons With Ruo 2 : Alcohols and Ethylenementioning
confidence: 99%
“…Both in ambient conditions and during intense illumination in vacuum, background C x H y and H 2 O has been observed to adsorb and dissociate on the surface [5][6][7][8], resulting in condensed carbonaceous and oxide contaminants at the nanolayer surface [9][10][11]. Atomic hydrogen exposure (AHE) [12][13][14][15] and atomic oxygen exposure (AOE) [16,17] are two viable options to selectively remove these contaminants, respectively via rehydrogenation, or via oxidation to volatile molecules. AHE has been reported to produce both metal and semiconductor surfaces entirely free of contamination [18].…”
Section: Introductionmentioning
confidence: 99%